The 16th Sabah State Election: Kadazandusun Politics and the Huguan Siou Factor - Tony Paridi, Bagang; Arnold, Puyok; Neilson Ilan, Mersat (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2021)
This article analyses the 16th Sabah State Election, focusing on the Kadazandusun-majority seats. It is based on an ethnographic study comprising interviews with candidates and casual conversations with local people in "competitive" Kadazandusun seats such as Matunggong, Kiulu, Moyog, Tambunan, Keningau, Sook, Nabawan, Tenom and Melalap. The results of the election showed that the Kadazandusun voted for status quo. In addition, following the trend of GE14, the Gabungan Rakyat Sabah (GRS) managed to maintain its strong presence in the Kadazandusun areas. This article argues that ethnic and personality politics play an instrumental role in determining the Kadazandusun support to GRS particularly STAR (Parti Solidariti Tanah Airku Rakyat Sabah/Homeland Solidarity Party) and PBS (Parti Bersatu Sabah/Sabah United Party). While economic factors are decisive as well, the role of the Kadazandusun traditional leadership institution is pertinent in influencing the people’s decision to vote.